2017
DOI: 10.1016/j.enpol.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Scalable off-grid energy services enabled by IoT: A case study of BBOXX SMART Solar

Abstract: This case study intends to show how Internet of Things (IoT) technology can be used to tackle development challenges by using the case study of BBOXX-a Solar Home Systems provider operating in South-Western Kenya and across Rwanda, and its SMART Solar platform applied to nearly 20,000 currently active systems. It aims to highlight the benefits of such technology to its users and how it can be utilised to create scalable business models for energy access through improved customer understanding. However, it also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Interconnected SHS-based microgrids, on the other hand, can scale just as wide as SHS, but also grow in size due to interconnectivity. AC/DC DC [16,40,42] AC [50], DC [49,51] or hybrid AC DC [32] Community loads/PUE No If planned, yes Yes Yes, depending on the microgrid size [32] Scalability & adoption Very high but limited to tier 2/3…”
Section: Shs-based Microgridmentioning
confidence: 99%
See 1 more Smart Citation
“…Interconnected SHS-based microgrids, on the other hand, can scale just as wide as SHS, but also grow in size due to interconnectivity. AC/DC DC [16,40,42] AC [50], DC [49,51] or hybrid AC DC [32] Community loads/PUE No If planned, yes Yes Yes, depending on the microgrid size [32] Scalability & adoption Very high but limited to tier 2/3…”
Section: Shs-based Microgridmentioning
confidence: 99%
“…Internet of things (IoT) is increasingly being used for implementing smart SHS to facilitate easy data acquisition and analysis. For example, BBOXX used its SMART Solar platform in nearly 20,000 SHS to better understand the user needs, enabling them to create scalable business models for energy access [42]. This leads to not just better user insights but also faster service and higher SHS user satisfaction.…”
mentioning
confidence: 99%
“…As inferred above, the existing literature is at best patchy and a long way from providing any comprehensive overview of what is a rapidly expanding and metamorphosing phenomenon. A literature search using Scopus, Web of Science, Science Direct, and Google Scholar, together with direct approaches to authors of some of the papers these searches identified to ask if they were aware of other literature we had missed, resulted in identification of only five articles in mainstream academic journals [8,9,12,18,19], seven articles in practitioner journals [20][21][22][23][24][25][26], and six detailed reports [5,7,10,11,27,28]. Of these latter, three were produced by the global mobile operators' key trade association (the GSMA) [7,11,27], one by researchers from UC Berkeley based on a study commissioned by the World Bank [10], one by the World Resources Institute [5], and one by an independent think tank, the Consultative Group to Assist the Poor [28].…”
Section: Coverage Of Existing Literaturementioning
confidence: 99%
“…In the case of the three aforementioned peer-reviewed analyses, these data have facilitated sophisticated analysis that is able to look in detail at the practices of consumers. Some commentators also note that PAYG businesses themselves are using the remote data to which PAYG affords access in order to generate consumer debt-financing risk profiles, as well as discussing the potential need for developing more centralised risk profiles, available to all actors across the sector, in efforts to facilitate the scaling up of PAYG-based services [7,11]. Whilst access to such data does facilitate interesting and insightful analysis (e.g., see our discussion of social practices later in this section), there are significant potential ethical issues related to the use of such data, issues that some authors acknowledge [12] and others note as having arisen as salient concerns within focus groups with PAYG users [10].…”
Section: Coverage Of Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation